One-loop N-point superstring amplitudes with manifest d=4 supersymmetry - Berkovits, N.; Vallilo, B. C. (Elsevier B.V., 2002)
The hybrid formalism for the superstring is used to compute one-loop amplitudes with an arbitrary number of external d = 4 supergravity states. These one-loop N-point amplitudes are expressed as Koba-Nielsen-like formulas with manifest d = 4 supersymmetry. (C) 2002 Published by Elsevier B.V. B.V.